A leitura na formação do universitário e suas intervenções nos processos educativos: formas de interação com o meio - Farenzena, Deline (My University, 2014)
The present dissertation, which is linked to the research line: Education, Language and Technologies, of the Pos-Graduation Program in Education PPGEd/UCS, researches the literary reading while a social practice inserted naturally in the family, at the school and in the society. In this way, it takes as a start point, individuals who live in a community of rural zone and are characterized as graduated people (with superior course). Its objective is to analyse how the reading of literary works can contribute for the personal and professional improvement of graduated people, from observation and confirmation of their social and professional activities, and how this can affect others in their community, in the development of reading practice. Therefore, it is important to mentionate that this study is linked to the research project ´Relation between efficient professional and reading TEAR 5´. Among its theoretical basis are: the concept of enlightenment/autonomy of Kant (2002) and Freire (1996); the historicity of reading which is supported in Cavallo and Chartier (1998); Lajolo and Zilberman (1999; 2002); studies about textual/discursive genres, from which are part the conceptions of Bakhtin (2003) and Bronckart (2003) and studies about the elaboration of reading strategies, which are based on Solé (1998). The data analysis is made with a base on Petit (2008; 2009) who deals a little with mediation; but it also has fundaments in Kant (1998) and in Jauss (1994) to discuss the question of aesthetic pleasure. These bases search to focus mainly in the reader´s formation, proposing an ethical and aesthetic view of the reality around, which many times is found in the fictional literature. This investigation which is characterized as qualitative and has fundaments in the ethnography, it was developed with graduated people from Monte Bérico Community, located in the interior of Veranópolis/RS, during 2009 and 2010. From the method is part, the realization of visits to the researched individuals, in which were observed the existence of reading materials in their residences or the presence of some familiar reading at the moment of the visit. Equally, questionnaires were applied. These instruments were used with the intention of a representative sample acquisition about the reading realized by the graduated people. So, from this frame, reading circles were elaborated, with the initial objective to provide to the participants of this research a bigger contact with the literary text. The workshops were organized aiming to start from the chronicles, for then, to enlarge the reading universe of the researched individuals, offering other texts of this nature. In this way, the reading circles aimed to not only achieving the reader or turning possible the change of experiences among them, but to engage the graduated people in the realization of a social work with their community. So, the data analysis gives signs of, front of a graduated people group who hardly read literary texts, the need to investigate and to keep up more with which importance is being given to the literary reading, as much at the school as in the community, and from this, to think in the space which is its, in the university. But, for this to be made, this study turned possible to notice and then, to think again in a decisive element of education, which is the teacher´s formation. This discussion is based mainly on Perrenoud (2002) and Rojo (2000).
A presente dissertação, que está vinculada à linha de pesquisa Educação, Linguagem e Tecnologias do Programa de Pós-Graduação em Educação PPGEd/UCS, investiga a leitura literária enquanto prática social inserida naturalmente na família, na escola e na sociedade. Dessa forma, ela toma como ponto de partida, indivíduos que habitem uma comunidade de zona rural e que se caracterizem como egressos de curso superior. Seu objetivo é então, analisar como a leitura de obras literárias pode contribuir para o aperfeiçoamento pessoal e profissional de egressos de curso superior, a partir de observações e constatações de suas atividades profissionais e sociais, e de como isso pode afetar as pessoas de sua comunidade, no desenvolvimento de práticas de leitura. Logo, é importante mencionar que esse estudo encontra-se vinculado ao projeto de pesquisa Relação entre profissional eficiente e leitura TEAR 5 . Dentre seus pilares teóricos estão: o conceito de esclarecimento/autonomia de Kant (2002) e Freire (1996); a historicidade da leitura com base em Cavallo e Chartier (1998), Lajolo e Zilberman (1999; 2002); estudos sobre gêneros textuais/discursivos, dos quais fazem parte as concepções de Bakhtin (2003) e Bronckart (2003) e estudos sobre a elaboração de estratégias de leitura, que se apóiam em Solé (1998). A análise dos dados é feita com base em Petit (2008; 2009) que trata um pouco a respeito de mediação; mas, também se fundamenta em Kant (1998) e Jauss (1994) para discutir a questão do gosto estético. Tais pilares buscam focalizar principalmente a formação do leitor, propondo-lhe uma visão ética e estética da realidade que o cerca, visão esta que muitas vezes se encontra fundamentada na literatura ficcional. Esta investigação que se caracteriza como qualitativa e tem bases na etnografia, foi desenvolvida com egressos de curso superior da Comunidade de Monte Bérico, localizada no interior de Veranópolis/RS, durante 2009 e 2010. Do método, faz parte a realização de visitas aos sujeitos da pesquisa, nas quais se buscou observar a existência de materiais de leitura em suas residências ou a presença de algum familiar lendo no momento da visita. Igualmente foram aplicados questionários. Tais instrumentos foram usados com vistas à obtenção de uma amostra representativa da leitura realizada pelos egressos. Sendo assim, a partir de tal quadro foram então elaboradas rodas de leitura, com o objetivo inicial de proporcionar aos participantes desta pesquisa maior contato com o texto literário. As oficinas foram elaboradas visando partir da leitura de crônicas literárias, para então, ampliar o universo de leitura dos sujeitos da pesquisa oferecendo-lhes outros textos dessa natureza. Dessa forma, as rodas de leitura objetivaram não apenas atingir o leitor ou possibilitar a troca de experiências entre eles, mas engajar os egressos de curso superior na realização de um trabalho social com sua comunidade. Assim, a análise dos dados dá indícios de que, diante de um grupo de egressos de curso superior que pouco leem textos literários, há a necessidade de investigar e acompanhar ainda mais que importância está sendo dada à leitura literária, tanto na escola quanto na comunidade, e a partir disso, pensar no espaço que a ela cabe conquistar na universidade. Mas, para que isso possa ser feito, esse estudo possibilitou perceber e então, repensar um elemento decisivo da educação, que é a formação do professor. Discussão essa, fundamentada principalmente em Perrenoud (2002) e Rojo (2000).
Keywords: Educação; Leitor autônomo; Educação; Formação profissional; Leitura literária; Leitura; Professores - Formação; Educação; Textos literários; Psicologia da leitura; Educação social; Autonomous reader; Education; Professional formation; Literary reading; Reading; Teachers, Training of; Education; Literary texts; Reading, Psychology of; Social Education